Ancestry and somatic profile indicate acral melanoma origin and prognosis - Patricia Basurto-Lozada; Martha Estefania Vázquez-Cruz; Christian Molina-Aguilar; Amanda Jiang; Dekker C. Deacon; Dennis Cerrato-Izaguirre; Irving Simonin-Wilmer; Fernanda G. Arriaga-González; Kenya L. Contreras-Ramírez; Emiliano Ferro-Rodríguez; Jamie Billington; Eric T. Dawson; et al. (Nature, 2026)
Abstract Acral melanoma, which is not ultraviolet-associated, is the type of melanoma reported most commonly in several non-European-descent populations 1–3 , including in Mexican people 4 . Latin American samples are substantially under-represented in global cancer genomics studies 5 , which directly affects patients in these regions as it is known that cancer risk and incidence may be influenced by ancestry and environmental exposures 6–8 . To address this, we characterized the genome and transcriptome of 123 acral melanoma tumours from 92 Mexican patients—a population notable because of its genetic admixture 9 . Compared with other studies of melanoma, we found fewer mutations in classical driver genes such as BRAF , NRAS or NF1 . Although most patients had predominantly Amerindian genetic ancestry, those with higher European ancestry had increased frequency of BRAF mutations. The tumours with activating BRAF mutations had a transcriptional profile more similar to cutaneous non-volar melanocytes, indicating that acral melanomas in these patients may arise from a distinct cell of origin compared with other tumours arising in these locations. Transcriptional profiling defined three expression clusters; these characteristics were associated with recurrence-free and overall survival. Our study enhances knowledge of this understudied disease and underscores the importance of including samples from diverse ancestries in cancer genomics studies.